Pengembangan Metode Rapid Test Preparation Dalam Penentuan Kadar Inherent Moisture dan Total Sulfur Dengan Menggunakan Metode yang Dipergunakan oleh ISO (International Organization for Standardization)) - Lumban Gaol Veronica Destiana; Aman Sentosa Panggabean; Rudi Kartika (JURNAL ATOMIK, 2017)
The research about the development of rapid test method in determination of inherent moisture concentration and total sulfur which used by the ISO (International Organization for Standardization) has been diving. This research aims to determine is the rapid test method could be used to analyze inherent moisture and total sulfur to determine the analytical performance of the rapid test. Parameters of the validation used in this research are accuracy which described in percent of recovery as the percent of the recovery of inherent moisture are 99,98 % and total sulfur value are 98,57 %, precision described in coefficient of the variant which gained in inherent moisture are 0,49% and total sulfur value is 4,1%. Robustness of method is described in the variation of drying time, which accuracy and precision do not affect by time variation in preparation. The results show that rapid test method can be used for an alternative method which used by the ISO.